Techno-economic assessment of polyhydroxyalkanoates production from lignocellulosic biomass employing halophilic and thermophilic microbial platform: Effect of fermentation conditions and downstream operations - Ozturk, Abdullah Bilal; Kourilova, Xenie; Buchtikova, Iva; Obruca, Stanislav (Waste management (New York, N.Y.), 2025)
This study investigates the techno-economic viability of synthesizing polyhydroxyalkanoates (PHA) from lignocellulosic biomass through the utilization of extremophilic microorganisms, framed within the context of Next-Generation Industrial Biotechnology (NGIB). Microbial platforms characterized by halophilic and thermophilic properties, specifically Halomonas halophila and Caldimonas thermodepolymerans, were utilized to tackle issues related to sterility demands, process efficiency, and sustainability. Scenarios incorporating rice straw and discarded softwood, which are low-cost feedstocks that do not interfere with the human food supply, were modeled as resources for PHA biosynthesis. Additionally, a comparison was conducted between traditional chloroform extraction methods and environmentally friendly hypotonic lysis for the recovery of PHA from extremophilic microbial cultures prone to this treatment. Economic indicators such as net present value, internal rate of return, and payback period, were analyzed to evaluate the economic viability of the process. Findings indicate that the incorporation of extremophilic microorganisms alongside waste valorization techniques could make PHA production economically viable, thereby decreasing dependence on fossil-derived plastics while simultaneously addressing ecological issues. This initial study highlights the necessity for subsequent scale-up investigations to authenticate the proposed methodology, which shows potential for the sustainable production of PHA.
Keywords: biotechnologie; lignin; Halomonas; Lignin; Caldimonas thermodepolymerans; Techno-economic assessment; Biotechnology; biomasa; polyhydroxyalkanoáty; Polyhydroxyalkanoates; Biomass; fermentace; Halomonas halophila; Process simulation; Fermentation